Pengembangan Ekonomi Mengatasi Kemiskinan Umat: Analisis Pemberdayaan Jemaat GPM Riring Rumahsoal - Josepina Supulatul; Martha Patty (Program Pascasarjana UKIM, 2022)
This article analyzes the concept of economic development for the congregation of Riring Rumahsoal through the cultivation of the red zalacca plant to face poverty issues. This congregation has abundant natural products but they are still living on the poverty line. The aim of the research is to find out the theological views of the congregation members towards red zalacca as God's gift for human life in meeting the needs of life and to know the church's concrete actions in processing red zalacca. The research method used in this study is qualitative research. The results of the research show that the church missions are still on the ritual aspect. The church has not optimally empowered the people's economy by utilizing natural products that can be used as a source of family income. Congregational development is rooted in ecclesiology which directs itself to church praxis which includes various individual and group activities. Therefore, the building of the church does not only limit its function to the rituals but also the church should conduct the congregational development from an economic aspect, by empowering every available natural potential to meet the needs of the people's lives.